(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The research results showed that, we could conclude that the type and color of seeds do not significantly affect the main of agronomic valuable traits. There was a weak correlation between some traits. The type and color of the undercut can be used as a marker attribute in breeding.